Recurrent massive hemoptysis from distal pulmonary pseudoaneurysms complicating invasive aspergillosis in a teenager - Caroline Mora-Soize, MD; Aline Carsin-Vu, MD MSc; Gratiela Mac Caby, MD; Nasredine Belkessa, MD; Claude Marcus, MD PhD; Sebastien Soize, MD PhD (Radiology Case Reports, 2022)
Invasive pulmonary aspergillosis in children rarely complicates life-threatening massive hemoptysis. Here, we report the case of a 15-year-old girl with acute lymphoblastic leukemia who was hospitalized for fever and medullary aplasia 1 month after beginning chemotherapy for invasive pulmonary aspergillosis. Despite voriconazole and caspofungine treatment, excavation of some lesions caused a unilateral small pneumothorax and bilateral pleural effusion, justifying intensive care management. The massive hemoptysis that occurred on day 23 was complicated with heart failure, and the patient was promptly resuscitated. Fibroscopy and computed tomography angiography (CTA) did not reveal the origin or cause of the bleeding. A second massive bleeding event occurred on day 32, and heart failure resolved after 10min of low flow. A new CTA showed 2 pseudoaneurysms of the subsegmental pulmonary arteries that were treated with embolization. Sedation was gradually decreased owing to improvement in respiratory status, but the patient did not regain consciousness because of deep brain sequelae. A limitation of care was decided upon, and the patient died in the following weeks. Massive hemoptysis is a rare life-threatening complication of invasive pulmonary aspergillosis, especially in children. Pulmonary artery pseudoaneurysms are unusual and should be detected as soon as possible to guide therapy. Intensive care management should be followed by embolization if the patient is stable; otherwise, surgery is indicated, ideally after identifying the source of bleeding by CTA or bronchoscopy. Early CTA follow-up can be proposed if the source of bleeding is still unknown as pseudoaneurysms can appear or grow rapidly.